Cozy christmas ebook - Hansen, Valerie (The Heart of Main Street., 2023)
A loner finds love in time for the holidays with a woman determined to unearth his small town's secrets in this inspirational romance. For the first time in years, Christmas brings hope to Bygones, Kansas. But for Josh Barton, Main Street's coffee shop owner, it brings back sad memories he'd rather forget. He's a new man, with a new life and faith now. Still, he hides a huge part of himself from his neighbors—and from one very inquisitive reporter. Whitney Leigh seems determined to uncover the mystery of the town's recent windfall, and Josh could help her. But that would mean opening up his guarded heart. Can a man who thought family and Christmas were only for others find a forever home where he least expects? The Heart of Main Street: They're rebuilding the town one step—and heart—at a time.